MENGEMBANGKAN KARAKTER JIWA SENI KRIYA PESERTA DIDIK MELALUI MATA PELAJARAN MUATAN LOKAL - Liantoni, Liantoni (Graduate Program Magister Manajemen Pendidikan, 2018)
This study aimed at decibing the local Scales Lessons that teach in school can develop the soul character of the craft for learners. This research was conducted at SMA Negeri 6 Talang Ubi, Penukal Abab Lematang Ilir, South Sumatera Province using descriptive qualitative approach with phenomenology method. The data obtained are expressed in the form of words used in SMA Negeri 6 Talang Ubi and presented in the form of narrative descriptions. Explanation of the research problem was obtained based on interviews, facts and events. Results showed that (1) local content was taught for equipping learners to know and love nature, social, culture, and spiritual in their area; (2) subjects of local content conducted to learners with program studentsâ development, competence needs, flexibility, and usefulness; (3) subjects of local content may consist of art, workshop, physical education and health, language and technology; (4) Art of Crafts is an object of local content that is taught by utilizing useful and valuable goods.